A Reading of the Third â€œVespersâ€ by Louise GlÃ¼ck - Am, Muhammad Dirgantara Esa Valentino (Universitas Sanata Dharma, 2020)
This paper presents a reading of the third â€œVespers,â€ a poem by Louise GlÃ¼ck collected in The Wild Iris, a book of poem sequence spoken by four different voices, dealing with the fact of human existence in the world, especially in terms of human existential suffering. To this date, this award-winning book has been considered by many to be among the poetâ€™s greatest achievements. This being the case, there have been so few detailed readings of the 54 poems constituting the book, however.Â Most of the existing scholarships on the poems are topic-centered rather than poem-centered. This article attempts to make its contribution to this by presenting a close reading of one of the poems, which is especially central to this polyphonic book both thematically and structurally. Assuming the critical premises and the analytical procedure of Helen Vendler, whose focus is on a poemâ€™s intrinsic elements and its relations to its thematic features, the paper discusses the third â€œVespersâ€â€™s theme as expressed by both its obvious and minute features. By analyzing the poemâ€™s title, body, internal structure, diction, tense, mechanic, rhythm, syntax, and imagery, the paper concludes that the poem expresses and dramatizes, through the obvious and minute details, the perennial theme of humanâ€™s pining for explanation about his/her discontent, which in the cosmos of the poem is directed to God, and its attendant feelings of doubt and conviction as a result of having to come up with his/her own answer as the one who holds the definite answer stays silent.Â